Network analysis of the symptoms of posttraumatic stress disorder in patients undergoing chemotherapy for colorectal cancer - Zhou, Yi; Teng, Wen; Luo, Liang; Zhou, Ping; Fan, Guidi; Liu, Haiying (Frontiers in Psychiatry, 2025)
ObjectiveIn this study, we examine the network structure of posttraumatic stress disorder (PTSD), including core symptoms and strong edges in patients undergoing chemotherapy for colorectal cancer in China, and lay the groundwork for targeted psychological interventions for these patients.MethodsThis study included 360 colorectal cancer patients receiving chemotherapy at a third-class hospital in Wuxi, China, from November 2023 to June 2024. The severity of each item of PTSD was assessed using the DSM-5 Checklist (PCL-5). A network analysis approach was conducted in R to pinpoint core symptoms and investigate notable edge connections within the network.ResultsThe accuracy and stability of the PTSD network structure model were relatively good, and the results indicated that robust connections emerged between avoidance of thoughts and avoidance of reminders, hypervigilance and exaggerated startle response, and loss of interest and detachment. The most central node was emotional cue reactivity, which was more closely connected with other symptoms, while self-destructive/reckless behavior was the lowest central node.ConclusionEmotional cue reactivity was proved to be the most prominent symptom in the PTSD symptom network in colorectal cancer patients treated with chemotherapy, and targeting it in interventions could lead to substantial improvements.